Hubungan penggunaan antibiotik empiris terhadap outcome terapi pasien community acquired pneumonia (CAP) di RSUP Fatmawati Jakarta - Feri Setiadi; Magdalena Niken Oktovina; Umi Salamah; Tengku Nadiah Fadillah (Universitas Jenderal Achmad Yani Yogyakarta, 2021)
Backgrounds: Community Acquired Pneumonia (CAP) is an inflammation of the lungs that is mostly caused by bacteria. Based on the 2018 Basic Health Research (RISKESDAS) data, the prevalence of pneumonia has increased every year, namely in 2013 (1.8%) and in 2018 (2.0%).Objective: This study aims to describes the relationship between empirical antibiotic use and empirical antibiotic use on the therapeutic outcome of CAP patients.Methods: This study was conducted retrospectively with a cross sectional method on CAP patients who met the inclusion criteria in the period January–December 2019.Results: The results of the study were patients aged 17-65 years 48 patients (65.8%), for male gender 39 patients (53.4%). The use of a single antibiotic ceftriaxone (42.5%) and a combination antibiotic ceftriaxone+levofloxacin (35.6%). Cephalosporin group of antibiotics (50.7%) and a combination of cephalosporin+quinolone group (42.5%).Conclusion: The longest duration of antibiotic use was in the range of 1-7 days (90.4%). The results of analysis of Chi-Square resulted having a Value of 0.75 (> 0.05), meaning that there was no relationship between the duration of empirical antibiotic use on the patient's therapeutic outcome (CAP). The duration of empirical antibiotic use has a value of 0.025 (<0.05), meaning that there is a relationship between the duration of the use of empirical antibiotics on the patient's therapeutic outcomes (CAP).